Towards a health-conscious transportation planning: A framework for estimating health impacts of active transportation at local level. (September 2021) - Peng, Binbin; Erdoğan, Sevgi; Nasri, Arefeh A.; Zou, Zhenpeng
Abstract: Introduction: The inter-relationship between physical activity and health is well-documented in transportation and public health literature. Nevertheless, health impacts are rarely considered in transportation planning processes due to the lack of a robust mechanism to quantify such impacts. The Integrated Transport and Health Impact Modeling (ITHIM) framework provides an opportunity to systematically estimate health impacts of active travel as a result of variations in transportation infrastructure and policies that involve non-motorized modes. Methods: This study applies ITHIM framework to Prince George's County, Maryland, to explore potential health impacts of improved active travel through hypothetical scenarios. ITHIM integrates data on travel behavior, health, demographics, road injuries and air quality. We constructed three What-If scenarios that reflect significant increases in walking and biking –a potential result of the ambitious infrastructure plans in place at the PG County – and decrease in personal vehicle miles. Results: Significant health and economic benefits are observed under three scenarios. We observed considerable health benefits in the scenarios where we made assumptions about increased active travel and reduced automobile usage, e.g. if everyone bikes 1.5 miles and drives 1.5 miles less per day, the county will save about 35 lives and 1, 443 DALYs. We also observed significant monetary values of lifesaving in the economic analysis, indicating 117 million savings in the cost of illness (COI) for scenario1 (increased walking) and 34 million savings in COI as a result of scenario2 (increased biking) and scenario3 (increased biking and reduced driving). Conclusion: This study provides insight into a better understanding of the potential health impacts of various transportation planning scenarios and provides an example for including health impact estimates in evaluating transportation policies and plans at local level. It highlights the importance of policies that encourage people to walk and bike also need to adopt measures that increase safety. Highlights: Integrated Transport and Health Impact Modeling (ITHIM) is an effective tool. Despite traffic injuries and air pollution risk, active travel is beneficial. Health benefits are higher when active travel increases, and automobile use reduces. Health impacts can be incorporated in evaluating transportation projects and plans.